Evaluation in Dynamic Process Spillover Effect: Eleven Major Exchange Rate Markets - Huang, Chun-Chieh (Asian Economic and Financial Review, 2015)
This paper analyzes the dynamic process of the spillover effects among major eleven exchange rate markets. The period spanning from 2000 to 2014 includes several financial crises and Chinese monetary reforms. By the vector auto regression framework, the evidence presents strong spillover effects in terms of return and volatility among USD and several currencies, especially for HKD. High scores of the return and volatility indices are found spilling from ten currencies to HKD.